Telaah kritis upaya peninjauan kembali dalam perkara perceraian di peradilan agama perspektif mashlahat al-mursalah - Misran Misran; Dhiauddin Tanjung; Pagar Pagar (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2024)
This paper aims to analyze the impact and legal consequences of extraordinary legal efforts for judicial review in the religious courts of divorce cases from the perspective of mashlahat al-mursalah. The method used is normative legal research using multiple approaches including legislation, cases, and a comparative approach with data analysis techniques using descriptive analysis methods. The conclusion of this study shows that legal remedies for judicial review of divorce cases that have permanent legal force (inkracht van gewijsde) create new problems (mafsadat) in society, so for the sake of legal certainty, it is better if legal remedies taken against divorce cases are sufficient to the level of appeal. or just appeal. The Compilation of Islamic Law (KHI) has a strategic position to regulate the provisions of the procedural law, considering that the position of KHI so far has not only played a role in regulating material law, it also regulates formal law against Muslim divorces in Indonesia.